Eco-innovative Activity of Ukrainian SMEs - Nataliya Horin (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The study attempts to investigate the eco-innovative activity of Ukrainian enterprises according to their size (small, medium, and large) with special focus on SMEs as the predominant group of enterprises, which ensure the innovative development of the whole national economy, and is central to the efforts to achieve environmental sustainability and green growth. The empirical analysis is based on a questionnaire survey of 254 Ukrainian enterprises of different sizes; the survey presents data on their current state and foreign trade activity, opportunities and barriers for the implementation of technological innovations and eco-innovations. The relationships between the export and eco-innovative activities is also explored. The analysis showed that SMEs are less eco-innovative in comparison with large enterprises, have fewer numbers of exporters than large firms, but exporters are more eco-innovative than non-exporters. Also, the size of the Eco-innovation Index for Ukraine was calculated. Based on the obtained results, Ukraine is an economy with a low level of eco-innovativeness, so, the study is extremely important.